Evolutionary economics and household behavior - Charles Yuji Horioka (University of the Philippines, School of Economics (UPSE), 2014)
This paper provides an introduction to the field of evolutionary economics with emphasis on the evolutionary theory of household behavior. It shows that the goal of evolutionary economics is to improve upon neoclassical economics by incorporating more realistic and empirically grounded behavioral assumptions and technological innovation and that the goal of the evolutionary theory of household behavior is to improve upon the neoclassical theory of household behavior by replacing the neoclassical assumption of selfish utility maximization with bounded rationality and satisficing and by incorporating the reaction of households to the introduction of new goods and services. The paper concludes with a brief discussion of loss aversion and self-interest vs. altruism.
Keywords: A12; B15; B25; B52; D11; D91; E21; O31; O33; 330; altruism; altruistic bequest motive; behavioral assumptions; behavioral economics; bequest motives; bounded rationality; consumption behavior; creative destruction; destructive technologies; dynastic bequest motive; evolution; evolutionary biology; evolutionary economics; group selection; household behavior; kin selection; loss aversion; natural selection; neoclassical economics; observational implicationsprofit maximization; pure altruism; rationality; reciprocal altruism; satisficing; selfishness; self-interest; strategic bequest motive; survival of the fittest; technology; technological innovation; technological progress; utility maximization